nüstyle – a neo-generative fashion lifestyle center facilitating circular economy and eco-consciousness in the fashion industry - Dy, Mariella Bernice de Cadiz
The fashion industry is the second most polluting and energy-intensive sector, generating 92 tons of textile waste annually due to fast-fashion’s linear economy and its throwaway culture. While slow fashion offers more eco-friendly alternatives with its circular economy model which emphasizes a closed-loop system that extends the garment's lifecycle, reducing waste and promoting sustainability. Despite this, there is an evident gap in the knowledge and awareness of consumers, fashion designers, and manufacturers on which sustainable strategies are the most effective; impeding them from developing their eco-consciousness. While others are unable to transition due to the lack of resources. Hence, the lack of consumer, designer, and manufacturer awareness, as well as the fragmented nature of the industry, hinders the progress of sustainability initiatives. This study aims to bridge the gap between these issues by employing a systems thinking approach to analyze the linear and circular fashion systems and their relationships. By utilizing interviews, observations, and precedents as references to create an inclusive fashion lifestyle center rooted in a circular economy, equipped with resources that enable the pursuit of reuse and repurposing of clothing, in turn promoting eco-conscious decision-making amongst its constituents. This highlights the importance of spatial design and organization as tools to create efficient and immersive spaces that will catalyze the transition towards a more sustainable fashion industry.